The Middle of Things : Essays. - Florian, Meghan (Wipf and Stock Publishers, 2017)
In the tradition of classic essayists from Virginia Woolf to Annie Dillard, Meghan Florian combines personal narrative with careful analysis, taking the ordinary material of undramatic daily life and distilling it into moments of clarity and revelation. Centering each essay in this collection on a different aspect of coming of age as a feminist woman within the ethos of the theological academy and the church, Florian interrogates the problems that arise when trying to inhabit these seemingly incompatible spheres, illuminating aspects of work, relationships, and daily life as a young woman. Par.